2017
DOI: 10.1016/j.ydbio.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific requirements for WNT11 in developing outflow tract and dorsal mesenchymal protrusion

Abstract: Correct cardiac development is essential for fetal and adult life. Disruptions in a variety of signaling pathways result in congenital heart defects, including outflow and inflow tract defects. We previously found that WNT11 regulates outflow tract development. However, tissue specific requirements for WNT11 in this process remain unknown and whether WNT11 is required for inflow tract development has not been addressed. Here we find that germline Wnt11 null mice also show hypoplasia of the dorsal mesenchymal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
(124 reference statements)
1
14
0
Order By: Relevance
“…Prior mouse genetic studies have revealed that the PCP pathway is critical for OFT formation in mammals. Loss of the presumptive PCP ligands Wnt5a and Wnt11 results in OFT malformation primarily in the form of PTA [63], and DORV or TGA [64, 65], respectively. Similarly, mutations of core PCP genes, including Fz1, 2, 7; Dvl1, 2, 3 ; and Vangl2 cause various OFT defects ranging from DORV, TGA to PTA [37, 61, 6669].…”
Section: Pcp Signaling In Mammalian Oft Developmentmentioning
confidence: 99%
“…Prior mouse genetic studies have revealed that the PCP pathway is critical for OFT formation in mammals. Loss of the presumptive PCP ligands Wnt5a and Wnt11 results in OFT malformation primarily in the form of PTA [63], and DORV or TGA [64, 65], respectively. Similarly, mutations of core PCP genes, including Fz1, 2, 7; Dvl1, 2, 3 ; and Vangl2 cause various OFT defects ranging from DORV, TGA to PTA [37, 61, 6669].…”
Section: Pcp Signaling In Mammalian Oft Developmentmentioning
confidence: 99%
“…Although the defects in these mutants have all been attributed to OFT shortening, the cause of which varies. Analysis of Wnt11 and Vangl2 revealed that they are required within OFT myocardium for cell polarization and organization during OFT elongation (Ramsbottom et al, 2014;van Vliet et al, 2017). In contrast, we and others have found that Wnt5a is highly expressed in the caudal SpM-SHF but not the OFT (Chen et al, 2012;Li et al, 2016;Sinha et al, 2015aSinha et al, , 2012.…”
Section: Introductionmentioning
confidence: 66%
“…In mice, germline deletion of Wnt5a, which encodes a presumptive mammalian PCP ligand, leads to CAT with almost full penetrance, whereas disruption of other PCP genes, Wnt11, Dvl1/2/3 and Vangl2 (Vang like 2), causes a spectrum of OFT defects from DORV to CAT (Etheridge et al, 2008;Person et al, 2010;Ramsbottom et al, 2014;Sinha et al, 2012;van Vliet et al, 2017). Although the defects in these mutants have all been attributed to OFT shortening, the cause of which varies.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the non-canonical Wnt pathway can also account for the cardiac and neural tube defects that occur later in embryo development. Wnt 11 and Fzd7 are required at multiple points during Xenopus heart development, not only early in the specification of cardiac progenitor cells, but also in cardiac morphogenesis (septation and outflow tract development) [5661]. The ensuing decreased activity of Dishevelled (Dvl) in Gam1 embryos is fully consistent with the cardiac and neural tube phenotypes of Dvl-deficient mice and Xenopus [6264].…”
Section: Resultsmentioning
confidence: 97%